Highly stereoselective diels-alder-based strategy for the synthesis of 3-epi-formicin A and 1-epi-formicin B - Khamkar, Sunil L.; Handore, Kishor L.; Shinde, Harish M.; Reddy, D. Srinivasa (Organic Letters, 2024)
The first enantioselective approach based on a highly stereoselective Diels-Alder reaction for the synthesis of 3-epi-formicin A and 1-epi-formicin B with rare N-acetylcysteamine-containing indenone thioesters is reported. The strategy utilizes a key Diels-Alder reaction to form the core hydrindane system with three contiguous stereocenters in very high levels of diastereo- and regioselectivity and one-pot oxidation/isomerization/dehydrogenation. The scope of this method was tested with different substrates to give cycloadducts in a highly diastereoselective manner.